Factors Affecting Students' Economics Learning Outcomes - Marmieti; Rika Verawati; Lovelly Dwinda Dahen (Journal of Practice Learning and Educational Development, 2026)
This study aims to analyze the influence of learning independence, learning discipline, parental attention, teaching style, and school environment on students’ learning outcomes in Economics at SMA Negeri 1 Sipora. The research employed a quantitative approach with a descriptive-associative method. The population consisted of 114 tenth-grade students, with a sample of 89 students selected through stratified random sampling. Data were collected using a closed questionnaire and analyzed using multiple linear regression. The results showed that partially: learning independence had a significant effect on learning outcomes (β=0.056; t=2.228>1.988), learning discipline had a significant effect (β=0.119; t=2.275>1.988), parental attention had a significant effect (β=0.184; t=4.504>1.988), teaching style had a significant effect (β=0.104; t=3.061>1.988), and school environment also had a significant effect (β=0.073; t=2.799>1.988). Simultaneously, the five variables significantly influenced learning outcomes with F=23.473>2.48. These findings emphasize that student learning outcomes are determined not only by internal factors but also by external factors.